Potret Pendidikan Nabi Ya’qub As Kepada Nabi Yusuf As - Muhammad Fahmi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2016)
The study in this article shows that the story of Prophet Yusuf Ya'qub and contains elements of education. The method of teaching which is reflected in the story of Prophet Yaqub and Yusuf-psychological form of interactive dialogue which provides a guide for action and reaction educators learners. While the competence of educators and ethics learners in the story of Jacob and Joseph can be described as the attitudes held by the subject of such learners, such as: patience, secrecy, develop talents individually, look at the social conditions in advance if it will deliver something, conjugate dreams, love, take advantage of the situation, it is easy to forgive, pray for others, and let go and submit to Allah SWT. As educators and learners, if able to implement educational pattern as described above, then God willing, will be born generation, superior and competitive because it is born of the pattern of Qur'anic education. Qur'anic education pattern is a pattern of education is always ascribe all the teaching material to the teachings of monotheism.